Synthesis of functionalized indolizines through 1,3-dipolar cycloaddition of zwitterionic ketenimines and pyridinium salts - Golmohammadi, Farhad; Osmani, Chiman; Rominger, Frank; Balalaie, Saeed (The journal of organic chemistry, 2025)
A straightforward and efficient strategy for the synthesis of fully functionalized indolizines has been developed through a transition metal- and oxidant-free [3 + 2] cycloaddition reaction of zwitterionic ketenimines and pyridinium salts. This versatile method proceeds under mild conditions, affording functionalized indolizines in moderate to good yields. This efficient approach involves an intermolecular [3 + 2] cycloaddition, followed by enamine/imine tautomerization and aromatization. Notably, this method demonstrates broad functional group compatibility and allows for facile scalability, making it a valuable tool for the synthesis of indolizine-based frameworks in organic and medicinal chemistry.
Online veröffentlicht: 19. April 2025
Gesehen am 29.09.2025